8th International Conference on Electrical and Computer Engineering 2014
DOI: 10.1109/icece.2014.7026871
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimal cost analysis of hybrid power system for Kutubdia island of Bangladesh

Abstract: Hybrid power system is the newest idea of utilizing renewable energy resources for generating electricity. Power generation largely depends on fossil fuel and as the total amount of reserved fossil fuel is decreasing we have to search for new resources for power generation. Hybrid power system usually demonstrates lower cost of production and higher reliability than the power system only using one renewable source. Geographically, Bangladesh is situated in an area having many renewable resources. Utilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The other parameters of the battery bank are described in Table 4. The converter used for DC-AC conversion has the foloowing characteristics; lifetime 15 years, the efficiency is considered 90%, the initial capital cost and replacement cost is being considered 310$ for converter size of 2 kW, the operating and maintenance cost is 50 ($/Unit-year) [38].…”
Section: Storage System and Converter Modelsmentioning
confidence: 99%
“…The other parameters of the battery bank are described in Table 4. The converter used for DC-AC conversion has the foloowing characteristics; lifetime 15 years, the efficiency is considered 90%, the initial capital cost and replacement cost is being considered 310$ for converter size of 2 kW, the operating and maintenance cost is 50 ($/Unit-year) [38].…”
Section: Storage System and Converter Modelsmentioning
confidence: 99%
“…The authors suggested a Solar/Wind/Biogas configuration with diesel generator as backup and battery to facilitate energy storage [7]. The large-scale power generation using only tidal or wind turbines is not economically a feasible option [39]. Thus, these two-energy system can be combined for costeffective energy supply.…”
Section: Introductionmentioning
confidence: 99%